DIABETES IS A DANGER THAT THREATENS OUR KIDS - Badr, Majdah; Zahem, A.K. Zahem; Motadares, G.M.; Baaqil, S.K. (Acta Scientiae et Intellectus, 2024)
This subject is very important in the life time because the people fetcher effect of sick for there, we bottom studied this subject for population in (K. S. A.) design increasing consciousness at the persons in population. Section 1, we discussed the definition of diabetes in children, type of diabetes in children, symptoms, complications of diabetes, methods of treatment in children, the measure glucose decrease in children, reasons for low blood glucose, signs and symptoms of low blood glucose, lower of blood glucose in children during sleep and diabetes prevention. Section 2, we project the result of questionnaire and write the statistical analysis for this subject and summaries on the results and illustration by figure.